Insights of antiparasitic activity of sodium diethyldithiocarbamate against different strains of Trypanosoma cruzi - de Freitas Oliveira, Johny Wysllas (2021)
Funding Information: This research was funded by Global Health and Tropical Medicine: Grant number IHMT-UID/multi/04413/2013 and Grant number PTDC/CVT-CVT/28908/2017, FCT-Portugal. Funding Information: We would like to thank Prof. João Aristeu da Rosa and Dr. Aline Rimodi Rimeiro at UNESP (Universidade Estadual de São Paulo) Araraquara (Brazil) for offering four different strains of T. cruzi. JWFO, CJGM, and BAC thanks to the financial support (PhD and Post-doctoral fellowships) provided by Capes/Brazil; MSS and HAOR thanks to CNPq/Brazil for the Research Grant (Bolsa de Produtividade). We also would like to thank the Department of Materials Engineering at UFRN for allowing the use of their scanning electron microscope, and the Department of Biochemistry at UFRN for allowing the use of their Flow Cytometer. We are also grateful to Paulo Fanado for editing this manuscript. Publisher Copyright: © 2021, The Author(s).